A Atuação do Ministério Público do Estado do Pará frente à garantia das condições mínimas de saúde para o justo cumprimento de pena no cárcere - LIMA, Eliseu Oliveira (2021)
This research deals with the performance of the Public Prosecution Service of the State of Pará regarding the right to health of those who are deprived of their freedom. Although health is constitutionally protected as a social right, and the State has the duty to guarantee the necessary means for the application of this right, the right to health of those who are incarcerated, living in this condition of vulnerability, mainly because they cannot move to a certain health care unit, is not being guaranteed due to the State's failure to provide the minimum health conditions for the fair execution of the sentence. Given this omission, it is analyzed the action of this Ministerial Body that honors its institutional and constitutional functions, using the judicial measures to ensure the best conditions in prison with the guarantee of the right to health of the prisoners.